The Use of Quick Response Codes for Listening Comprehension in Junior High School - hidayati, nurul (RETAIN, 2021)
The study aims is to describe the use of QR Codes in listening comprehension for Junior High School and students’ responses toward the use of QR Codes in listening comprehension for Junior High School. This study used a descriptive qualitative method applied to eight grades of Junior High School through observation, interview, and questionnaire. The instruments used to collect the data among them are field notes, interviews sheet, and questionnaire in Google form. The results of the data showed that QR Codes are an appropriate medium to promote students’ listening skills because the use of QR Codes are simple and effective. Besides that, the use of QR Codes in learning listening in the class also got a positive response from students.